оценим каждое слагаемое
![image](https://tex.z-dn.net/?f=P%28x%29%3Dax%5E%7Bn%7D%2Ba_%7B1%7Dx%5E%7Bn-1%7D%2Ba_%7B2%7Dx%5E%7Bn-2%7D%2Ba_%7B3%7Dx%5E%7Bn-3%7D%2Ba_%7B4%7Dx%5E%7Bn-4%7D%2B...%2Ba_%7Bk%7Dx%5E%7Bn-k%7D%5C%5C%5C%5C%0A+-1+%5Cleq+x+%5Cleq+1+%5C%5C%5C%5C%0AP%281%29+%3D+a%2Ba_%7B1%7D%2Ba_%7B2%7D%2Ba_%7B3%7D%2Ba_%7B4%7D%2B....%2Ba_%7Bk%7D%3C1%5C%5C%5C%5C%0AP%281%29+%3D+a%2Ba_%7B1%7D%2Ba_%7B2%7D%2Ba_%7B3%7D%2Ba_%7B4%7D%2B....%2Ba_%7Bk%7D%3E-1%5C%5C%5C%5C+%0A)
-1\\\\
" alt="P(x)=ax^{n}+a_{1}x^{n-1}+a_{2}x^{n-2}+a_{3}x^{n-3}+a_{4}x^{n-4}+...+a_{k}x^{n-k}\\\\
-1 \leq x \leq 1 \\\\
P(1) = a+a_{1}+a_{2}+a_{3}+a_{4}+....+a_{k}<1\\\\
P(1) = a+a_{1}+a_{2}+a_{3}+a_{4}+....+a_{k}>-1\\\\
" align="absmiddle" class="latex-formula">
положим что
видно что
![P(2)=a*2^{n}+a_{1}*2^{n-1}+a_{2}*2^{n-2}+...+a_{k}*2^{n-k} \leq
P(2)=a*2^{n}+a_{1}*2^{n-1}+a_{2}*2^{n-2}+...+a_{k}*2^{n-k} \leq](https://tex.z-dn.net/?f=P%282%29%3Da%2A2%5E%7Bn%7D%2Ba_%7B1%7D%2A2%5E%7Bn-1%7D%2Ba_%7B2%7D%2A2%5E%7Bn-2%7D%2B...%2Ba_%7Bk%7D%2A2%5E%7Bn-k%7D++%5Cleq+%0A)
![image](https://tex.z-dn.net/?f=a%3D1%5C%5C%5C%5C%0AS_%7Bgeom%7D+%3D2%282%5En-1%29%3D2%5E%7Bn%2B1%7D-2%3C4%5En%5C%5C%5C%5C%5C%0A2%5E%7B2n%7D-2%2A2%5En%2B2%3E0%5C%5C%5C%5C%0AD%3C0%5C%5C)
0\\\\
D<0\\" alt="a=1\\\\
S_{geom} =2(2^n-1)=2^{n+1}-2<4^n\\\\\
2^{2n}-2*2^n+2>0\\\\
D<0\\" align="absmiddle" class="latex-formula">
а так как оценка идет сверху то она и справедлива снизу , верно